P1255DIASTOLIC BLOOD PRESSURE IS ASSOCIATED WITH BRAIN ATROPHY IN HEMODIALYSIS PATIENTS: A SINGLE CENTER CASE CONTROL STUDY. (6th June 2020) - Cohen-Hagai, Keren; Fanadka, Feda; Grumberg, Tania; Topaz, Guy; Nacasch, Naomi; Greenberg, Meidad; Zitman-Gal, Tali; Benchetrit, Sydney
Abstract: Background and Aims: Brain atrophy (BA) is a common finding in neuroimaging of hemodialysis (HD) patients, representing a parenchymal cerebral damage. Likely contributing factors to BA are age, chronic hypertension, diabetes mellitus and other cardiovascular risk factors of atherosclerosis that are also common among HD patients. BA may also occur due to focal ischemia and hypoperfusion during HD. However, data on optimal blood pressure (BP) in these patients are limited. The goal of this study was to determine whether the prevalence and severity of BA would be higher among HD patients with lower BP. Method: A blinded neuroradiologist graded BA of all HD patients who underwent brain non-contrast computerized tomography (CT) from 2015 to 2017 in our institution. Age-and sex-matched patients with normal kidney function who underwent brain CT during the same period and technique served as the control group Results: A total of 280 patients were included in this retrospective study, with average BP of 140/70 mmHg among HD patients and 142/75 mmHg in the control group. BA was more common in dialysis patients and its severity increased with age and traditional cardiovascular risk factors. We observed a significant negative correlation between diastolic BP (DBP) at dialysis initiation and BA. Average DBP decreased with increasing severity of BA. These findings were observed in both HD and non-CKD patients. Conclusion: Brain atrophy was associated with lower DBP, which may induce cerebral hypoperfusion and ischemia. This finding should discourage over-treatment of hypertension in hemodialysis patients.